Basic conditions for costless signalling in financial markets - Günter Franke (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1985)
A costless, fully revealing signalling equilibrium is derived from two easily understandable conditions. The outsidet-protection condition states that the outsiders relate the price which they offer to pay for a security inversely to the supply of this security which they interpret as a quality signal. Thereby they attempt to protect themselves against adverse selection. The noarbitrage condition requires that the exchange rate for two securities must be the same in both primary and secondary markets. These conditions have strong implications for the valuation of securities and optimal insider policies. Therefore a costless signalling equilibrium is obtained.
Keywords: 650